The deepest border : the Strait of Gibraltar and the making of the modern Hispano-African borderland - Pack, Sasha D. (Stanford University Press, 2019)
This text presents the history of southern Iberia and the western Maghrib, and the Strait of Gibraltar between them, as a single bicontinental borderland, from roughly 1850 to 1970. Drawing on primary and secondary sources from several countries, it posits a long historical arc of transformation from a remote and hostile religious frontier into a multilaterally managed regional order.